2007
DOI: 10.1590/s0103-50532007000800009
|View full text |Cite
|
Sign up to set email alerts
|

Solid phase microextraction (SPME) analysis of volatile compounds produced by in vitro shoots of Lantana camara L. under the influence of auxins and cytokinins

Abstract: ) sobre o desenvolvimento e produção de compostos voláteis de plantas in vitro de Lantana camara L. Os voláteis foram extraídos por microextração em fase sólida (SPME) e analisados utilizando cromatografia com fase gasosa acoplada à espectrometria de massas (GC-MS). Plantas cultivadas in vitro, nos diferentes tratamentos, apresentaram aumento na produção de mirceno, α-felandreno, α-copaeno, trans-cariofileno e β-gurjuneno, e redução de α e β-pineno, quando comparadas com a planta matriz. on growth, development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 4 publications
2
10
1
Order By: Relevance
“…These data agree with those reported for leaf volatiles from A. zerumbet cultured in medium containing cytokinin, where data evidenced a large number of hydrocarbons in leaf volatiles when KIN and BAP were applied . Effects of cytokinins on the level of volatile compounds have been reported in tissue cultures of medicinal plants (Affonso et al, 2007). However, in this study, the addition of cytokinin did not improve methyl salicylate production in vitro cultures of P. paniculata, conversely a reduction in its content was observed in growing concentrations of BAP (Figure 3).…”
Section: Resultscontrasting
confidence: 50%
See 1 more Smart Citation
“…These data agree with those reported for leaf volatiles from A. zerumbet cultured in medium containing cytokinin, where data evidenced a large number of hydrocarbons in leaf volatiles when KIN and BAP were applied . Effects of cytokinins on the level of volatile compounds have been reported in tissue cultures of medicinal plants (Affonso et al, 2007). However, in this study, the addition of cytokinin did not improve methyl salicylate production in vitro cultures of P. paniculata, conversely a reduction in its content was observed in growing concentrations of BAP (Figure 3).…”
Section: Resultscontrasting
confidence: 50%
“…Tissue culture techniques have some advantages as physical and biological manipulation of medicinal plants under standardized conditions, use of elicitors and plant growth regulators to optimize bioactive compounds and subculturing of elite genotypes (Affonso et al, 2007;Victório et al, 2008;Victório et al, 2009;. The purpose of this study was to evaluate in vitro organogenesis of P. paniculata under standardized conditions and volatiles production using the growth regulator BAP (6-benzylaminopurine).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, volatile organic compounds (VOCs) have received special attention from the scientific community, as they have a wide range of biological and pharmacological uses and there are many publications related to the emission of volatiles [12]. Affonso et al [13] treated Lantana camara plants with high concentrations (0.44 and 4.4 µmol/L) of BA and showed an increase in the production of volatile compounds detected by solid phase microextraction (SPME). These include myrcene, α-phellandrene, α-copaene, trans-caryophyllene and β-gurjunene.…”
Section: Introductionmentioning
confidence: 99%
“…On another study by Marotti et al (1996) who found that the high economic value of basil oil is attributable to the existence of phenyl propanoids, like eugenol, chavicol and their derivatives or terpenoids like monoterpen alchole linalool, methyl cinnamate, and limonene. Affonso et al (2007) mentioned that BA has also been used to enhance the growth and expansion of aromatic plants. Utilization Lantana camara L. plants with BA at 0.44 and 4.4 μmol/L raised volatile organic ingredient (VOC) production, which was detected by solid phase micro-extraction.…”
Section: Volatile Oil Componentsmentioning
confidence: 99%
“…BA has additionally been used to enhance the growth and development of aromatic flowers. Treating Lantana camara L. flora with BA increased unstable natural compound production as volatile oil contents (Affonso et al, 2007). Similarly, Zielińska et al (2011) indicated that the production of volatile oil contents elevated with the utility of various PGRs, such as indole-3acetic acid (IAA), thidiazuron, kinetin, and BA, when applied to Agastache rugosa flowers grown in vitro.…”
Section: Introductionmentioning
confidence: 99%